Analysis and Design Information System Logistics Delivery Service in Pt Repex Wahana - Surja, Stephanie; Sanjaya, Lius Steven (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Analysis and Design of Logistic Delivery System in PT Repex Wahana aims to analyze company?s need in existing business process of logistic delivery service. This will then be used in the development of an integrated system that can address the problems in the running process of sending and tracking the whereaboutsor status of the delivered goods which are the core business processes in the enterprise. The result then will be used as basis in the development of integrated information system in pursuit of corporate solution for process business automation, delivery process, inventory, and logistic delivery tracking, which is the core of the company business process, and it will be documented using Unified Modeling Language. The information system is meant to simplify the delivery and tracking process in the company, besides will minimize lost and error of data which is often happened because of the manual and unorganized transaction data processing.